A method for manufacturing a chip interconnect ceramic substrate based on copper sintering process
By adopting the chip interconnected ceramic substrate production method based on copper sintering process in the field of semiconductor packaging, the problems of high material costs, thermal mismatch and interconnection degradation in traditional silver sintering processes are solved, and lower cost and higher reliability products are achieved.
Patent Information
- Application Number
- CN202411897494.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-23
- Publication Date
- 2025-04-04
AI Technical Summary
The traditional silver sintering process has problems such as high material costs, thermal mismatch caused by mismatch of thermal expansion coefficients, high requirements for metallization layer on the substrate surface, and interconnection degradation in the field of semiconductor packaging.
The chip interconnected ceramic substrate production method based on the copper sintering process is adopted. Through screen printing, SPI detection, pressure patching, baking and sintering, uniform printing and curing of copper paste is achieved, reducing material costs and improving thermal performance.
It significantly reduces material costs, improves the competitiveness of the product in the price-sensitive market, alleviates the problem of thermal mismatch, extends the service life of the product, and improves the reliability and stability of the product.
Smart Images

Figure CN119764177A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the field of semiconductor packaging, and in particular to a method for manufacturing a chip interconnect ceramic substrate based on a copper sintering process. Background Art
[0002] In the field of semiconductor packaging, the interconnection process between chips and substrates has always been one of the key technologies. Traditionally, the silver sintering + DTS process is widely used. However, with the development of technology and changes in market demand, this traditional process has gradually exposed some significant shortcomings.
[0003] As a precious metal, silver is relatively expensive, which makes material cost an issue that cannot be ignored in large-scale production. The high cost of raw materials limits the competitiveness of products in price-sensitive markets and also increases the production costs and operating pressure of enterprises.
[0004] In terms of thermal performance, the thermal expansion coefficient of silver is significantly different from that of commonly used chip materials (such as silicon carbide) and substrate materials (such as ceramics). Under the working conditions of thermal cycling and power cycling, this mismatch in thermal expansion coefficient can easily lead to thermal mismatch problems, which in turn affects the reliability and stability of the product. Thermal mismatch may cause connection failure, cracks, and other problems, shortening the service life of the product.
[0005] Traditional processes have high requirements for the metallization layer on the substrate surface, which increases the complexity and cost of substrate preparation. The quality and characteristics of the metallization layer on the substrate surface have a key impact on the connection effect. Any tiny flaws or mismatches may lead to an unstable connection interface.
[0006] In addition, the silver sintering process is prone to interconnection degradation phenomena such as atomic diffusion and intermetallic compound formation during long-term use, which will lead to increased contact resistance and thermal resistance at the interface, affecting current distribution and heat transfer efficiency, and further reducing product performance and reliability. Summary of the invention
[0007] In view of the problems existing in the above-mentioned prior art, the present invention provides a method for manufacturing a chip interconnect ceramic substrate based on a copper sintering process, which can effectively solve the problems existing in the above-mentioned prior art.
[0008] The technical solution of the present invention is:
[0009] According to one aspect of the present invention, the following steps are included:
[0010] S1, install the screen template on the screen printing equipment, place the copper paste slurry on one end of the screen, move the scraper on the screen, make the copper paste slurry pass through the pores of the screen, and print on the connection part of the chip and the AMB ceramic substrate. The thickness of the printed copper paste is 60-80μm;
[0011] S2, SPI testing of copper paste printed on AMB ceramic substrate;
[0012] S3, using a pressure mounter to mount the chip on the copper paste of the AMB ceramic substrate, the thickness of the copper paste after the chip is mounted is 40-80 μm; in an oxygen-free environment, the AMB ceramic substrate after the chip is mounted is baked to initially solidify the copper paste;
[0013] S4, after the chip and the AMB ceramic substrate are sintered, plasma cleaning is performed;
[0014] S5, attaching the DTS material to the connection part between the chip and the AMB ceramic substrate;
[0015] S6, sintering the chip, AMB ceramic substrate and DTS material in an oxygen-free environment.
[0016] Furthermore, in step S1, the size of the silk screen opening is 85-92% of the size of the chip pad.
[0017] Furthermore, in step S1, the pressure of the scraper is 0.45-0.5 kg / 25 mm, and the speed of the scraper is 20-40 mm / s.
[0018] Furthermore, in step S3, the AMB ceramic substrate after chip mounting is placed in a constant temperature drying oven for baking, the oxygen content in the oven is less than 500 ppm, the baking temperature is 145-155° C., and the baking time is 35-45 minutes.
[0019] Furthermore, in step S6, the chip, the AMB ceramic substrate and the DTS material are placed in a pressure sintering furnace for sintering. The sintering temperature is 270-290° C. and the sintering time is 7-10 minutes.
[0020] Further, in step S3, the printed copper paste and the AMB ceramic substrate are placed in a constant temperature drying oven for baking, the oxygen content in the oven is less than 100 ppm, the baking temperature is 95-110° C., and the baking time is 9-12 min;
[0021] The pressure mounter is used to mount the chip on a predetermined position of the AMB ceramic substrate;
[0022] Then, the AMB ceramic substrate with the chip mounted thereon is placed in a pressure sintering furnace for sintering, and an inert gas is introduced into the pressure sintering furnace. The sintering temperature is 240-280° C., and the sintering time is 280-320 seconds.
[0023] Furthermore, the inert atmosphere is nitrogen or argon.
[0024] By adopting the above technical solution, the present invention has the following beneficial effects compared with the prior art:
[0025] First, in terms of cost, since the price of copper is much lower than that of silver, only a few tens of times that of silver, the cost is greatly reduced from the perspective of raw material value. This advantage is particularly prominent in large-scale production, significantly reducing the material cost pressure of enterprises, enhancing the price competitiveness of products in the market, and creating greater profit space for enterprises.
[0026] Secondly, in terms of performance, the thermal expansion coefficient of copper materials is closer to that of silicon carbide chips and ceramic substrates, which can effectively alleviate the thermal mismatch problem under thermal and power cycling conditions. This greatly improves the reliability and stability of the product under different temperature environments, significantly reduces problems such as connection failure caused by thermal expansion differences, extends the product's service life, and reduces maintenance costs.
[0027] Third, in terms of process adaptability, the copper sintering process is insensitive to the metallization layer on the substrate surface, which greatly simplifies the connection interface structure. This not only reduces the difficulty and cost of substrate preparation, but also improves the stability of the interface and the reliability of the product, and reduces the risk of poor connection and failure caused by problems with the metallization layer on the substrate surface.
[0028] Fourth, in terms of inhibiting interconnection degradation, the simple copper sintering interface composition can maximally inhibit interconnection degradation phenomena such as atomic diffusion and intermetallic compound formation. Moreover, compared with silver, copper can effectively avoid the silver migration problem generated during the silver sintering process, further reduce the contact resistance and thermal resistance at the interface, optimize the current distribution, improve the performance and stability of the product, and ensure the efficient operation of the product in long-term use. In addition, copper has a higher melting point, which makes its theoretical material fatigue performance better than silver. This is manifested in higher reliability and longer service life in practical applications. The results of thermal shock tests and power cycle reliability tests both show that the reliability of copper sintering modules is significantly higher than that of silver sintering modules. At the same time, equipment suitable for silver sintering processes can be well compatible with high-performance copper slurries, which provides convenient conditions for the application of copper sintering. Enterprises do not need to replace production equipment on a large scale, which reduces the cost of technology conversion and is conducive to the rapid promotion and widespread application of copper sintering technology. BRIEF DESCRIPTION OF THE DRAWINGS
[0029] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.
[0030] Figure 1This is a schematic diagram of the steps of the manufacturing method of Example 1 in the present invention;
[0031] Figure 2 This is a schematic diagram of the steps of the manufacturing method of Embodiment 2 of the present invention;
[0032] Figure 3 Schematic diagram of C-SAM results after silver sintering power cycle test;
[0033] Figure 4 This is a schematic diagram of the C-SAM results after the copper sintering power cycle test of the present invention;
[0034] Figure 5 This is a curve chart of silver sintering PC test results;
[0035] Figure 6 This is a curve diagram of the copper sintering PC test results of the present invention;
[0036] In the picture: chip-1, silver paste-2, copper paste-3. DETAILED DESCRIPTION
[0037] The present invention will be further described in detail below in conjunction with the accompanying drawings and examples. It is particularly noted that the following examples are only used to illustrate the present invention, but are not intended to limit the scope of the present invention. Similarly, the following examples are only partial embodiments of the present invention rather than all embodiments, and all other embodiments obtained by those of ordinary skill in the art without creative work are within the scope of protection of the present invention.
[0038] like Figure 1 and Figure 2 As shown, this solution provides a method for manufacturing a chip interconnect ceramic substrate based on a copper sintering process.
[0039] Embodiment 1:
[0040] See also Figure 1 , a method for manufacturing a chip interconnect ceramic substrate based on a copper sintering process, comprising the following steps:
[0041] S1, using high-precision screen printing equipment, according to the connection requirements of the chip and the AMB ceramic substrate, a specific screen template is made. The process of making the screen template is a direct application of the prior art, and the specific process steps of making the screen template are not repeated here. The first embodiment of this invention is a wet pasting process. Because of the fluidity of the copper paste, when the copper paste is printed on the AMB ceramic substrate and is ready to be pasted with the chip, the contact between the chip and the AMB ceramic substrate will produce a certain pressure, and the weight of the chip will also act on the copper paste. Since the copper paste has fluidity in the wet pasting stage, this pressure and weight will cause the copper paste to deform and displace, causing the copper paste to overflow to the back of the entire chip, which may cause short circuits or other electrical connection problems. Therefore, the size of the screen opening is 85-92% of the size of the chip pad. Preferably, the size of the screen opening is 89-90% of the size of the chip pad. When the size of the screen opening is slightly smaller than the size of the chip pad, the flow range of the copper paste during the printing process can be effectively limited. By reducing the size of the screen opening, the copper paste is prevented from overflowing to the chip surface. Although the size of the silk screen opening is smaller than the pad size, as long as the opening size is properly designed, such as the preferred 89-90%, it can still ensure that enough copper paste is printed on the pad to form a good electrical connection, which can both ensure the reliability of the connection and avoid excessive overflow of copper paste.
[0042] The screen template is installed on the screen printing equipment, and the copper paste slurry is placed at one end of the screen. The scraper is moved on the screen to make the copper paste slurry pass through the pores of the screen and print on the connection part of the chip and the AMB ceramic substrate. The thickness of the printed copper paste is 60-80 μm. The pressure of the scraper is 0.45-0.5 kg / 25 mm. Preferably, the pressure of the scraper is 0.49-0.5 kg / 25 mm, and the speed of the scraper is 20-40 mm / s. To ensure that the thickness of the printed copper paste can be 60-80 μm.
[0043] S2, SPI detection of copper paste printed on AMB ceramic substrate; SPI detection usually uses special detection equipment, which uses high-precision image acquisition and processing technology to monitor and analyze the solder paste printed on the substrate in real time. Commonly used SPI detection methods include optical microscopy, X-ray fluorescence spectroscopy (XRF), thermal imaging, acoustic imaging, AOD method, 3D scanning method and FFT (Fast Fourier Transform) method, etc., and the SPI detection method is not limited here. Through SPI detection, problems in the copper paste printing process, such as uneven copper paste thickness, missing, contamination, etc., can be discovered in time, thereby ensuring the quality and reliability of the subsequent welding process.
[0044] S3, use a pressure mounter to mount the chip on the copper paste of the AMB ceramic substrate. The thickness of the copper paste after mounting the chip is 40-80μm; preferably, the thickness of the copper paste after mounting the chip is 40-50μm. The copper paste is a conductive medium between the chip and the ceramic substrate, and its thickness uniformity and appropriateness are crucial to achieve good electrical connection. If the copper paste is too thin, it may cause poor electrical connection, increase contact resistance, and affect signal transmission and power loss. Controlling the thickness within the range of 40-50μ can ensure that the copper paste fully fills the gap between the chip and the substrate to form a good conductive path. In an oxygen-free environment, the AMB ceramic substrate after chip mounting is baked to remove the solvent in the copper paste slurry and make the copper paste initially solidified; the AMB ceramic substrate after chip mounting is placed in a constant temperature drying oven for baking. The oxygen-free or low-oxygen environment can significantly reduce the risk of oxidation of the copper paste and the chip during baking. The metal components in the copper paste are easy to react with oxygen at a higher temperature, resulting in performance degradation or defects. Therefore, the oxygen content in the box is less than 500ppm. By controlling the oxygen content to be less than 500ppm, this situation can be effectively avoided. The oxygen-free or low-oxygen environment helps the organic matter and solvent in the copper paste to volatilize and decompose more evenly, thereby promoting the curing process of the copper paste, which helps to improve the bonding force between the solidified copper paste and the AMB ceramic substrate and the chip, and enhance the overall mechanical strength and electrical properties. The baking temperature is 145-155°C, preferably, the baking temperature is 148-150°C, and the baking time is 35-45min, preferably, the baking time is 38-40min. The choice of baking time is crucial to the degree of curing of the copper paste. If the baking time is too short, the copper paste may not be initially cured, resulting in performance problems in subsequent processing and use; if the baking time is too long, it may cause excessive oxidation or burning of the copper paste, which will also affect its performance. Therefore, the baking time is selected to be 35 to 45 minutes, preferably 38 to 40 minutes to ensure that the copper paste is initially cured.
[0045] S4, after the chip and AMB ceramic substrate are sintered, plasma cleaning is performed to effectively remove tiny pollutants and oxide layers on the surface of the chip and AMB ceramic substrate, improve the cleanliness and activity of the surface, and create good conditions for subsequent DTS mounting.
[0046] S5, attaching DTS material to the connection between the chip and the AMB ceramic substrate can further enhance the reliability and performance of the connection between the chip and the AMB ceramic substrate; DTS material is a direct application of the existing technology, and its principle and structure are not described in detail here.
[0047] S6, sinter the chip, AMB ceramic substrate and DTS material in an oxygen-free environment to further strengthen the connection between the chip and the AMB substrate. The chip, AMB ceramic substrate and DTS material are placed in a pressure sintering furnace for sintering at a temperature of 270 to 290°C. Preferably, the sintering temperature is 275 to 280°C. The sintering temperature is between 275 and 280°C. The atomic diffusion rate between the chip, AMB ceramic substrate and DTS material is moderate, which is conducive to forming a tight connection. Excessive sintering temperature may lead to a decrease in material properties, such as reduced thermal stability and weakened mechanical strength. The appropriate sintering temperature can maintain the original properties of the material while ensuring the quality of the connection. Reasonable sintering temperature can reduce energy consumption and reduce energy waste in the production process. At the same time, the appropriate sintering temperature can also reduce material waste and rework costs caused by excessive sintering.
[0048] The sintering time is 7 to 10 minutes. Preferably, the sintering time is 8 to 9 minutes. If the sintering time is too short, the connection between the chip, AMB ceramic substrate and DTS material may not be tight enough, and there may be pores or incompletely fused areas, thus affecting the reliability and mechanical strength of the connection. The sintering time is between 8 and 9 minutes, which can ensure that the materials are fully fused and diffused to form a strong connection. If the sintering time is too long, it may cause excessive fusion of the material, unnecessary thermal stress, and even damage to the material structure, such as grain growth and crack generation. Reasonable sintering time can ensure the quality of the connection while avoiding the negative effects of excessive sintering.
[0049] Embodiment 2:
[0050] See also Figure 2 , a method for manufacturing a chip interconnect ceramic substrate based on a copper sintering process, comprising the following steps:
[0051] S1, install the screen template on the screen printing equipment, place the copper paste slurry at one end of the screen, move the scraper on the screen, let the copper paste slurry pass through the pores of the screen, and print it on the connection part of the chip and the AMB ceramic substrate. The thickness of the printed copper paste is 60-80μm; the size of the screen opening is 1.05-1.1 times the size of the chip pad, preferably, the size of the screen opening is 1.1 times the size of the chip pad. The pressure of the scraper is 0.45-0.5kg / 25mm, preferably, the pressure of the scraper is 0.49-0.5kg / 25mm, and the speed of the scraper is 20-40mm / s. To ensure that the thickness of the printed copper paste can be 60-80μm.
[0052] S2, SPI detection of copper paste printed on AMB ceramic substrate; SPI detection usually uses special detection equipment, which uses high-precision image acquisition and processing technology to monitor and analyze the solder paste printed on the substrate in real time. Commonly used SPI detection methods include optical microscopy, X-ray fluorescence spectroscopy (XRF), thermal imaging, acoustic imaging, AOD method, 3D scanning method and FFT (Fast Fourier Transform) method, etc., and the SPI detection method is not limited here. Through SPI detection, problems in the copper paste printing process, such as uneven copper paste thickness, missing, contamination, etc., can be discovered in time, thereby ensuring the quality and reliability of the subsequent welding process.
[0053] The main difference between the second embodiment and the first embodiment is step S3. In the second embodiment, the chip and the AMB ceramic substrate are bonded using a dry bonding process, which is as follows:
[0054] S31, put the printed copper paste and AMB ceramic substrate into a constant temperature drying oven for baking, remove the solvent in the copper paste slurry, make the copper paste initially solidified, and the oxygen content in the box is less than 100ppm. In this embodiment, the copper paste is first baked and initially solidified, so there is no chip attached to the surface of the copper paste, and the copper paste is more exposed to oxygen. Therefore, compared with Example 1, the oxygen content of the drying oven in this embodiment needs to be lower, and the metal components (such as copper) in the copper paste are prone to oxidation reaction in the presence of oxygen. Oxidation not only causes changes in the properties of the copper paste surface, but also may affect its subsequent connection performance and electrical properties with the chip. Therefore, reducing the oxygen content in the drying oven can effectively prevent the oxidation of the copper paste during the baking process and maintain its original chemical and physical properties. During the baking process, the copper paste needs to go through the stage of solvent volatilization and initial solidification. At this stage, if the oxygen content is too high, it may interfere with the curing process of the copper paste, resulting in incomplete curing or decreased curing quality. By reducing the oxygen content, the oxygen content in the box is less than 100ppm, which can create an environment that is more conducive to the curing of the copper paste, thereby improving the curing quality and ensuring that the connection between the copper paste and the AMB ceramic substrate is more secure.
[0055] The baking temperature is 95-110°C, preferably 100-105°C. The baking temperature is within the range of 95-110°C, especially within the preferred range of 100-105°C, which can ensure that the solvent in the copper paste is fully volatilized. The rapid volatilization of the solvent is conducive to the rapid drying and preliminary solidification of the copper paste. The baking time is 9-12 minutes, preferably 10-11 minutes; the baking time is 9-12 minutes, especially 10-11 minutes, which is conducive to the close bonding between the copper paste and the AMB ceramic substrate, thereby improving the electrical performance and mechanical stability of the component.
[0056] S32, use a pressure mounter to mount the chip on a predetermined position of the AMB ceramic substrate; the thickness of the copper paste after mounting is 40-80μm, and preferably, the thickness of the copper paste after mounting the chip is 40-50μm. The copper paste is a conductive medium between the chip and the ceramic substrate, and its thickness uniformity and appropriateness are crucial to achieve good electrical connection. If the copper paste is too thin, it may cause poor electrical connection, increase contact resistance, and affect signal transmission and power loss. Controlling the thickness within the range of 40-50μ can ensure that the copper paste fully fills the gap between the chip and the substrate to form a good conductive path.
[0057] S33, then put the AMB ceramic substrate with the chip mounted into a pressure sintering furnace for sintering, and inert gas is introduced into the pressure sintering furnace, preferably, the inert atmosphere is nitrogen or argon. Inert gas has the characteristic of not being easy to react with other substances, and can form an oxygen-free or low-oxygen environment during high-temperature sintering, effectively preventing the metal components (such as copper particles) in the copper paste and the chip and AMB ceramic substrate from being oxidized, and oxidation can cause the material performance to decline, affecting the quality and reliability of the product. The introduction of inert gas can ensure that the material maintains its original chemical and physical properties during the sintering process. Inert gas can also disinfect and sterilize the oil stains and microorganisms such as bacteria and viruses on the surface of the material, which is beneficial to the quality control of the product.
[0058] The sintering temperature is 240-280°C, preferably 250-260°C, to ensure good connection between copper particles and avoid thermal damage to the chip and AMB ceramic substrate. The sintering time is 280-320s, preferably 300-310s; the sintering time should be long enough to allow the sintering reaction to proceed fully, but not too long to cause over-sintering.
[0059] S4, after the chip and AMB ceramic substrate are sintered, plasma cleaning is performed to effectively remove tiny pollutants and oxide layers on the surface of the chip and AMB ceramic substrate, improve the cleanliness and activity of the surface, and create good conditions for subsequent DTS mounting.
[0060] S5, attaching the DTS material to the connection between the chip and the AMB ceramic substrate; the reliability and performance of the connection between the chip and the AMB ceramic substrate can be further enhanced; the DTS material is a direct application of the existing technology, and its principle and structure are not described in detail here.
[0061] S6, sinter the chip, AMB ceramic substrate and DTS material in an oxygen-free environment to further strengthen the connection between the chip and the AMB substrate. The chip, AMB ceramic substrate and DTS material are placed in a pressure sintering furnace for sintering at a temperature of 270 to 290°C. Preferably, the sintering temperature is 275 to 280°C. The sintering temperature is between 275 and 280°C. The atomic diffusion rate between the chip, AMB ceramic substrate and DTS material is moderate, which is conducive to forming a tight connection. Excessive sintering temperature may lead to a decrease in material properties, such as reduced thermal stability and weakened mechanical strength. The appropriate sintering temperature can maintain the original properties of the material while ensuring the quality of the connection. Reasonable sintering temperature can reduce energy consumption and reduce energy waste in the production process. At the same time, the appropriate sintering temperature can also reduce material waste and rework costs caused by excessive sintering.
[0062] The sintering time is 7 to 10 minutes. Preferably, the sintering time is 8 to 9 minutes. If the sintering time is too short, the connection between the chip, AMB ceramic substrate and DTS material may not be tight enough, and there may be pores or incompletely fused areas, thus affecting the reliability and mechanical strength of the connection. The sintering time is between 8 and 9 minutes, which can ensure that the materials are fully fused and diffused to form a strong connection. If the sintering time is too long, it may cause excessive fusion of the material, unnecessary thermal stress, and even damage to the material structure, such as grain growth and crack generation. Reasonable sintering time can ensure the quality of the connection while avoiding the negative effects of excessive sintering.
[0063] The following are the C-SAM results after power cycle test of silver paste sintering and copper paste sintering under thermal shock conditions of -40℃-175℃:
[0064] See also Figure 3 and Figure 4 , Figure 3 C-SAM results after silver sintering power cycle test, Figure 3 The darker area in the center is the silver paste 2, and the gray area between the silver paste 2 and the chip 1 represents the degradation phenomenon. It can be clearly seen that after the silver paste 2 has undergone power cycling, the edge of the silver paste 2 has been severely degraded.
[0065] Figure 4 C-SAM results after copper sintering power cycle test, Figure 4 The darker area in the center is copper paste 3, and the gray area between copper paste 3 and chip 1 represents degradation. It can be clearly seen that after power cycling, copper paste 3 has almost no degradation compared to silver paste 2.
[0066] from Figure 3 and Figure 4It can be clearly seen that under the thermal shock conditions of -40℃~175℃, the life reliability of sintered copper is about 30% higher than that of sintered silver, and no obvious interface damage is found in the sintered layer. After power cycling, the degradation of silver sintering is more serious than that of copper sintering. At the same time, under the constant current test conditions, under the same test life, the sintered silver layer has a more obvious degradation phenomenon, while the sintered copper layer is in good condition.
[0067] See also Figure 5 and Figure 6 , the horizontal axis in the figure represents the number of cycles (Cycle), and the vertical axis represents the temperature change (ΔT(j)[℃]). There are two curves in the figure, the red curve represents the temperature change at lower power or initial state; the blue curve represents the state at higher power or after a certain number of cycles.
[0068] Figure 5 This is the curve chart of silver sintering PC test results. Figure 6 This is a curve diagram of the copper sintering PC test results of the present invention, from Figure 5 and Figure 6 It can be seen from this data that under the same test conditions and the same number of power cycles, the junction temperature of silver sintering is higher than that of copper sintering. This means that copper sintering has higher reliability when subjected to long-term high-power cycles.
[0069] The above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit the same. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that the technical solutions described in the aforementioned embodiments may still be modified, or some of the technical features may be replaced by equivalents. However, these modifications or replacements do not deviate the essence of the corresponding technical solutions from the spirit and scope of the technical solutions of the embodiments of the present invention.
Claims
1. A method for manufacturing a chip interconnect ceramic substrate based on a copper sintering process, characterized in that: The following steps are involved: S1, install the screen template on the screen printing equipment, place the copper paste slurry on one end of the screen, move the scraper on the screen, make the copper paste slurry pass through the pores of the screen, and print on the connection part of the chip and the AMB ceramic substrate. The thickness of the printed copper paste is 60-80μm; S2, SPI testing of copper paste printed on AMB ceramic substrate; S3, using a pressure mounter to mount the chip on the copper paste of the AMB ceramic substrate, the thickness of the copper paste after the chip is mounted is 40-80 μm; in an oxygen-free environment, the AMB ceramic substrate after the chip is mounted is baked to initially solidify the copper paste; S4, after the chip and the AMB ceramic substrate are sintered, plasma cleaning is performed; S5, attaching the DTS material to the connection part between the chip and the AMB ceramic substrate; S6, sintering the chip, AMB ceramic substrate and DTS material in an oxygen-free environment.
2. The method for manufacturing a chip interconnect ceramic substrate based on a copper sintering process as claimed in claim 1, characterized in that: In step S1, the size of the silk screen opening is 85-92% of the chip pad size.
3. The method for manufacturing a chip interconnect ceramic substrate based on a copper sintering process as claimed in claim 1, characterized in that: In step S1, the pressure of the scraper is 0.45-0.5 kg / 25 mm, and the speed of the scraper is 20-40 mm / s.
4. The method for manufacturing a chip interconnect ceramic substrate based on a copper sintering process according to claim 1, characterized in that: In step S3, the AMB ceramic substrate after chip mounting is placed in a constant temperature drying oven for baking, the oxygen content in the oven is less than 500 ppm, the baking temperature is 145-155° C., and the baking time is 35-45 minutes.
5. The method for manufacturing a chip interconnect ceramic substrate based on a copper sintering process according to claim 1, characterized in that: In step S6, the chip, the AMB ceramic substrate and the DTS material are placed in a pressure sintering furnace for sintering. The sintering temperature is 270-290° C. and the sintering time is 7-10 minutes.
6. The method for manufacturing a chip interconnect ceramic substrate based on a copper sintering process according to claim 1, characterized in that: In step S3, the printed copper paste and AMB ceramic substrate are placed in a constant temperature drying oven for baking, the oxygen content in the oven is less than 100 ppm, the baking temperature is 95-110° C., and the baking time is 9-12 minutes; The pressure mounter is used to mount the chip on a predetermined position of the AMB ceramic substrate; Then, the AMB ceramic substrate with the chip mounted thereon is placed in a pressure sintering furnace for sintering, and an inert gas is introduced into the pressure sintering furnace. The sintering temperature is 240-280° C., and the sintering time is 280-320 seconds.
7. The method for manufacturing a chip interconnect ceramic substrate based on a copper sintering process as claimed in claim 6, characterized in that: The inert atmosphere is nitrogen or argon.